“OUTSIDE OF STORIES”: THE NARRATOR AND THE FLANEUR IN POE’S AND DOYLE’S DETECTIVE FICTION - Gonçalves, Davi; Batista, Eduarda (Revista Interfaces, 2024)
This study compares the characters of Dupin and Holmes from The murders in the Rue Morgue (1841)by Edgar Allan Poeand A study in scarlet (1887)by Arthur Conan Doyleconsidering the concept of flaneur brought up in the nineteenth century by Charles Baudelaire. Besides that, it analyzes the narration perspective and how it contributes to the construction of the detectives’ character in the story. Given the objectives, the procedures here will be reading both literary pieces along with the theoretical review selected in order to connect mass literature and canonic literature, demonstrating how every literary work can be investigated apart from its academic status. Finally, both characters proved to be compatible with the concept, as they are, indeed, outsiders who see what is hidden to other’s eyes. In addition, the narrator showed himself as someone much more closer to the reader, as their point of view is coherent with one another, making the characterization of the detectives easier to be decoded.